Legal Protection For Health Workers Against Hospital Safety And Health Standards - Ummi Rachmi Pasaribu*; Tamaulina Br Sembiring (Riwayat: Educational Journal of History and Humanities, 2024)
This paper discusses legal protection for health workers against safety and health standards in hospitals. Hospitals as work environments that pose special risks to health workers require adequate legal protection to ensure safe and healthy working conditions. This study identifies legal regulations governing safety and health standards in hospitals, and analyzes the implementation and effectiveness of such legal protection in daily practice. The method used in this research is a literature study to collect relevant legal data as well as a case study to illustrate the application and challenges in legal protection for health workers. The results of this study are expected to contribute to raising awareness of the importance of legal protection for health workers in hospitals, as well as recommendations for improvements in existing policies and practices.